2010
DOI: 10.1200/jco.2009.27.0090
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Risks of CNS Tumors in Survivors of Childhood Cancer: The British Childhood Cancer Survivor Study

Abstract: Purpose CNS tumours are the most common second primary neoplasm observed after childhood cancer in Britain, but the relationship of risk to dose of previous radiotherapy and chemotherapy is uncertain. Methods The British Childhood Cancer Survivor Study is a national population-based cohort study of 17980 individuals surviving at least 5 years after diagnosis of childhood cancer. Linkage to national population-based cancer registries identified 247 second primary neoplasms of the CNS. Cohort and nested case-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
127
2
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 19 publications
(36 reference statements)
3
127
2
8
Order By: Relevance
“…Additionally, we feel that the relatively high proportion of Grade II/III tumors may reflect a referral bias to our institution. Because past therapeutic radiation [12], BMI in females [13] and hormone replacement therapy [14] have been associated with the development of meningioma, we felt that assessing the association of these factors with the meningioma grade may be important. It should be noted that obesity is associated with higher adipose aromatase activity, estrogen, androgens, and insulin-like growth factor [15].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we feel that the relatively high proportion of Grade II/III tumors may reflect a referral bias to our institution. Because past therapeutic radiation [12], BMI in females [13] and hormone replacement therapy [14] have been associated with the development of meningioma, we felt that assessing the association of these factors with the meningioma grade may be important. It should be noted that obesity is associated with higher adipose aromatase activity, estrogen, androgens, and insulin-like growth factor [15].…”
Section: Discussionmentioning
confidence: 99%
“…30 Consistent with this conclusion, the largest study of population-based risk of malignancy after radiation exposure by dose demonstrated no significant increase in the relative risk of malignancy after exposure to 0.01-9.99 Gy. 27 Additionally, neurological and nonneurological risks of DSA in the infant population were recently reviewed at our institution with no increase in morbidity in this population. 11 All of this accumulating evidence suggests that the additional risk of favoring DSA over MRI/MRA in a follow-up protocol after AVM treatment is minimal, and unlikely to surpass the risk of hemorrhage from an undetected recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, radiation exposure is a major contributor to treatment related late morbidity for long-term survivors. Children are particularly susceptible to the late effects of radiation, even at low doses, as demonstrated in epidemiologic studies of exposed populations [2,3]. The reasons for this include the sensitivity of developing and growing tissues, the longer life expectancy resulting in a larger window of opportunity for expressing radiation damage, and the large number of long-term survivors.…”
Section: Introductionmentioning
confidence: 99%